Chapter Ao(s) espelho(s) do espaço e do tempo - Rita, Annabela (Studi e saggi, 2021)
The following work aims to explore some of the most peculiar paradigms of the travel narratives, focusing on aesthetic aspects as the metamorfoses of the view and schemes, which are the signal of the European culture's transformation.